2020
DOI: 10.3390/ijms21041189
|View full text |Cite
|
Sign up to set email alerts
|

Protein Expression Profile in Rat Silicosis Model Reveals Upregulation of PTPN2 and Its Inhibitory Effect on Epithelial-Mesenchymal Transition by Dephosphorylation of STAT3

Abstract: Silicosis is a chronic occupational lung disease caused by long-term inhalation of crystalline silica particulates. We created a rat model that closely approximates the exposure and development of silicosis in humans. Isobaric tags for relative and absolute quantitation (iTRAQ) technologies we used to identify proteins differentially expressed in activated rat lung tissue. We constructed three lentiviral knockdown vectors and an overexpression vector for the protein tyrosine phosphatase non-receptor type 2 (PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The repeated process of phagocytosis, necrosis and rephagocytosis of the cells induces inflammation and activation of the reactive oxygen species system, which is associated with pulmonary interstitial fibrosis [6][7][8]. Proteomic analysis has suggested that some proteins have been found to be closely related to the occurrence and development of silicosis [9,10]. Most proteins were enriched in immune system processes, oxygen transporter activity, phagosome, lysosome and extracellular matrix (ECM)-receptor interactions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The repeated process of phagocytosis, necrosis and rephagocytosis of the cells induces inflammation and activation of the reactive oxygen species system, which is associated with pulmonary interstitial fibrosis [6][7][8]. Proteomic analysis has suggested that some proteins have been found to be closely related to the occurrence and development of silicosis [9,10]. Most proteins were enriched in immune system processes, oxygen transporter activity, phagosome, lysosome and extracellular matrix (ECM)-receptor interactions [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, we applied TMT proteome to compare the lungs from silicosis mice with healthy controls, and successfully identi ed 1,742 differentially expressed proteins (≥ 1.2-fold change, p < 0.05) in silicosis mice. This is far above previous reports (471 differentially expressed proteins identi ed by iTRAQ [10]), and with highly improved detection precision.…”
Section: Discussionmentioning
confidence: 53%
“…After that, Na's group [9] reported 196 differentially expressed proteins (fold change ≥ 1.2) in silica-treated broblasts. And in 2020, Juxiang Yuan and his colleagues [10] examined lung tissues of silicosis mice and normal mice and identi ed 471 proteins differentially expressed proteins between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the mRNA and protein expression levels of LDHA were increased in rats that inhaled silica [ 10 , 11 ]. As the key enzyme in glycolysis, LDHA preferentially converts pyruvate to lactate.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that the mRNA and protein levels of lactate dehydrogenase A (LDHA) were upregulated in rats that inhaled silica [ 10 , 11 ], suggesting a potential role of LDHA in the glycolysis of silicosis. Increased levels of LDHA and its metabolic product, lactate, were found in patients with idiopathic pulmonary fibrosis (IPF).…”
Section: Introductionmentioning
confidence: 99%